2013
DOI: 10.1016/j.bbr.2012.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Daily treadmill exercise attenuates cocaine cue-induced reinstatement and cocaine induced locomotor response but increases cocaine-primed reinstatement

Abstract: Exercise affects neuroplasticity and neurotransmission including dopamine (DA), which modulates drug-taking behavior. Previous research in rodents has shown that exercise may attenuate the rewarding effects of drugs of abuse. The present study examined the effects of high and low exercise on cocaine responses in male Wistar rats that had been trained to self-administer and were compared to a group of sedentary rats. High exercise rats (HE) ran daily on a treadmill for 2 h and low exercise (LE) ran daily for 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 48 publications
(77 reference statements)
2
46
1
Order By: Relevance
“…For example, when rats are primed with cocaine following a period of extinction, forced physical activity on a treadmill increases cocaine seeking (Thanos et al, 2013). However, this same study found that forced physical activity decreases cue-induced reinstatement, which indicates the physical activity differentially activates neural systems involved in relapse to either cocaine or cocaine-associated cues.…”
Section: Subjectsmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, when rats are primed with cocaine following a period of extinction, forced physical activity on a treadmill increases cocaine seeking (Thanos et al, 2013). However, this same study found that forced physical activity decreases cue-induced reinstatement, which indicates the physical activity differentially activates neural systems involved in relapse to either cocaine or cocaine-associated cues.…”
Section: Subjectsmentioning
confidence: 73%
“…However, when access to a running wheel is implemented either before or after daily operant conditioning sessions, a decrease in intravenous self-administration also is obtained across different various drugs, including cocaine (Smith et al, 2008b;, methamphetamine (Engelmann et al, 2013;Miller et al, 2012), heroin (Smith and Pitts, 2012) and morphine (Hosseini et al, 2009). Physical activity also decreases the escalation of self-administration (Engelmann et al, 2013;Zlebnik et al, 2012) and reinstatement (Lynch et al, 2010;Sanchez et al, 2013;Thanos et al, 2013;Zlebnik et al, 2010). Especially relevant to human tobacco cessation treatments, physical activity also decreases reinstatement of nicotine seeking following a period of extinction .…”
Section: Preclinical Evidencementioning
confidence: 90%
“…Although levels of running do not consistently predict effects on the incubation of craving (6465), effects become more pronounced with increasing exercise access such that high access (≥6-hr/day) blocks the incubation effect (4647). Forced exercise at low-to-moderate levels also attenuate the incubation effect in response to cues and drug-primes; however, high levels of forced exercise increase drug-primed craving (49). These findings indicate that the efficacy of exercise at reducing drug-craving depend on the stimuli present in the environment and indicate the potential for forced exercise to increase craving.…”
Section: Sex Differencesmentioning
confidence: 99%
“…While lack of power and compliance issues undoubtedly contribute to the variability (2429,5659), results from animal studies also demonstrate that certain exercise conditions may not be effective, and some may even increase relapse vulnerability (44,49). The ability of exercise to reduce or enhance withdrawal symptoms/craving and relapse vulnerability is likely determined by the underlying neurobiology which can vary between males and females, exercise conditions, drugs of abuse, and early versus later abstinence time-points (2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in humans, the long-term efficacy of exercise at reducing smoking is controversial, 19 and there are several reports indicating that involvement in certain team sports can be associated with higher levels of drug use. 20,21 Although this latter finding is likely attributable in part to social factors, 22 findings in animals have also revealed that certain exercise conditions enhance rather than decrease addictionrelated behaviors 23,24 suggesting that biological factors may also contribute. Given that exercise is becoming more frequently considered as a potential treatment for addiction, it is critical to identify not only the conditions that produce beneficial effects, but also those that are ineffective or lead to detrimental effects.…”
Section: Introductionmentioning
confidence: 99%